Fundamentals and Applications of Topological Polarization Singularities - Wang , Feifan; Yin, Xuefan; Zhang, Zixuan; Chen, Zihao; Wang, Haoran; Li, Peishen; Hu, Yuefeng; Zhou, Xinyi; Peng, Chao (Frontiers in Physics, 2022)
Radiations towards the continuum not only brings non-Hermicity to photonic systems but also provides observable channels for understanding their intrinsic physics underneath. In this article, we review the fundamental physics and applications of topological polarization singularities, which are defined upon the far-field radiation of photonic systems and characterized by topological charges as the winding numbers of polarization orientation around a given center. A brief summarizing of topological charge theory is presented. A series of applications related to topological polarization singularities are then discussed.